2020
DOI: 10.1029/2019jb018213
|View full text |Cite
|
Sign up to set email alerts
|

Shear Velocity Inversion Using Multimodal Dispersion Curves From Ambient Seismic Noise Data of USArray Transportable Array

Abstract: We utilize an array method called the frequency‐Bessel transformation method to extract the multimodal dispersion curves of Rayleigh waves from ambient seismic noise data recorded by the USArray Transportable Array. We observe as many as five overtones' dispersion curves of Rayleigh waves in the Midwestern United States, and four and three overtones' dispersion curves, respectively, in the U.S. Great Plain area and Northeastern United States. We employ a quasi‐Newton method to invert the multimodal dispersion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 41 publications
(57 reference statements)
4
46
0
Order By: Relevance
“…However, although the F‐J method has been successfully applied to active and passive source data to extract multimode surface wave dispersion curves (Li & Chen, 2020; Wang et al., 2019; Wu et al., 2019; Yang et al., 2019), it currently can only deal with ZZ component CCFs. On the one hand, other‐component CCFs provide complementary information of the Earth's structure (Aki, 1957; Gribler & Mikesell, 2019; Haney et al., 2012; Xia, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, although the F‐J method has been successfully applied to active and passive source data to extract multimode surface wave dispersion curves (Li & Chen, 2020; Wang et al., 2019; Wu et al., 2019; Yang et al., 2019), it currently can only deal with ZZ component CCFs. On the one hand, other‐component CCFs provide complementary information of the Earth's structure (Aki, 1957; Gribler & Mikesell, 2019; Haney et al., 2012; Xia, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The F‐J method is very effective in extracting multimodal dispersion information of surface waves from array seismic records. In previous works (Li & Chen, 2020; Wang et al., 2019; Wu et al., 2020), the F‐J method is introduced and applied for the vertical seismic component only. In this study, we extend the F‐J method to account for the concerned seismic and electric components (i.e., u r , u z, and E r ).…”
Section: Methodsmentioning
confidence: 99%
“…The surface wave method, such as Rayleigh wave method or Love wave method, is an appealing noninvasive tool for estimating the subsurface shear wave velocity structures from seismic recordings generated by active source, passive source, or natural earthquake (e.g., Bensen et al., 2007; Li et al., 2019; Nakata et al., 2011; Shapiro et al., 2005; Shen & Ritzwoller, 2016; Xia et al., 1999). It has been widely applied in various fields, such as near‐surface geophysical exploration (e.g., Beaty et al., 2002; Cheng et al., 2016; Dal Moro et al., 2019; Foti et al., 2011; Park et al., 1999), and regional or global seismology (e.g., Lin et al., 2008; Wu et al., 2020; Yang et al., 2007; Yao et al., 2006). This method is based on the dispersion characteristic of surface waves, and can be divided into three main procedures: field data acquisition, dispersion curve extraction, and dispersion curve inversion (e.g., Park et al., 1999; Socco et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transportable Array (TA) have shown that the F-J method is very robust and efficient. Based on the overtones extracted by the F-J method, Wu et al (2020) demonstrated that overtones can significantly improve the nonuniqueness and convergence of the shear-wave velocity inversion.…”
Section: Introductionmentioning
confidence: 99%